Measurement of the anchoring force of covered self‐expandable and lumen‐apposing metal stents for interventional endoscopic ultrasonography. Issue 1 (25th August 2022) - Takasaki, Yusuke; Isayama, Hiroyuki; Shin, Kyoung Sub; Ishii, Shigeto; Fujisawa, Toshio; Moon, Jong Pil; Fukuma, Taito; Ushio, Mako; Takahashi, Sho; Suzuki, Akinori; Ito, Koichi; Tomishima, Ko
Abstract : Objectives: Interventional endoscopic ultrasonography is performed for various situations that require drainage, after which stent migration is the most severe adverse event. Several lumen‐apposing metal stents (LAMS) and covered self‐expandable metal stents (CSEMS) provide antimigration systems; however, their anchoring ability has not been studied well. Therefore, we measured and compared the anchoring force (ACF) of commercially available LAMS and CSEMS. Methods: Anchoring force was measured for five types of LAMS (NAGI, SPAXUS, Plumber, and AXIOS 8 and 10 mm) and seven types of CSEMS (BCL, SHCL, BCG, BPD [four types of HANAROSTENT], HILZO, Niti‐S [Spring Stopper], and Wallflex). We created a phantom model for inducing stent migration. It has a rotatable part as a curved fixture, and we measured ACF at angles between 0° and 40°. Results: The mean ACF at 0° and 20° were NAGI 1.50, 1.84 N, SPAXUS 1.73, 1.72 N, Plumber 2.64, 2.03 N, and AXIOS 3.96, 3.61 N, respectively; and BCL 0.48, 0.53 N, Wallflex 0.53, 0.48 N, SHCL 0.64, 0.73 N, HILZO 1.09, 1.09 N, BCG 1.22, 1.20 N, BPD 1.78, 1.67 N, and Spring Stopper 2.29, 2.51 N. Conclusion: We measured ACF in LAMS and CSEMS with a new phantom model. The highest value among the LAMS was for the AXIOS and among the CSEMS was for the Spring Stopper. Some of the ACF values varied with the direction of pull. These findings may have a significant impact on stent selection for interventional endoscopic ultrasonography, and this model can be used to evaluate newly developed stents.